MOLECULAR IDENTIFICATION OF CAPRA HIRCUS IN EAST CHIA SABZ, AN IRANIAN PRE-POTTERY NEOLITHIC SITE, CENTRAL ZAGROS, BASED ON MTDNA - F. H. Mazdarani; M. T. Akbari; 3; R. M. N. Fard; M. Hessari; K. C. Pour (Journal of Animal and Plant Sciences, 2014)
Since the beginning of livestock domestication in Near East in Neolithic era, human communities have benefited from goat (Capra hircus). Central Zagros has been identified as an independent center of Neolithization and goat domestication. The aim of this study was to assess the molecular analysis of five ancient goat samples belonged to East Chia Sabz, Central Zagros, Iran. Control region (HV1) of mitochondrial DNA was partially amplified and sequenced to compare the Neolithic goat haplotypes with modern goat haplotypes. In phylogenetic analysis, the five Neolithic sequences were grouped into A haplogroup which shows the early population expansion of dominant A lineage within Zagros in 9th millennium BC.
Keywords: Capra hircus; Central Zagros; mtDNA; Neolithic haplotypes